Intratumoral CD8+ tumor-infiltrating lymphocytes as prognostic predictors in radio-chemoradiotherapy-treated nasopharyngeal carcinoma - Li, Xinjing; Qiu, Xiaoming; Lin, Cuihong; Liu, Yuanying; Wang, Yongbin; Tang, Langlang; Tong, Yuanhe; Tang, Linbo (Frontiers in Oncology, 2025)
BackgroundThe prognostic value of tumor-infiltrating lymphocytes (TILs) in nasopharyngeal carcinoma (NPC) has been established. However, the prognostic significance of CD4+ and CD8+ TIL subtypes in NPC remains unclear.MethodsWe collected 214 tissue samples diagnosed with NPC for immunohistochemical staining. The density of CD4+ and CD8+ TILs was evaluated in intratumoral (within tumor cell nests) and stromal (the surrounding stroma of tumor cell nests) areas. Correlations between TIL density and progression-free survival (PFS) and overall survival (OS) were analyzed.ResultsHigh levels of intratumoral CD8+ TILs were significantly associated with reduced risk of disease progression (HR 0.382; 95% CI, 0.178-0.819, P = 0.013) and death (HR 0.265; 95% CI, 0.104-0.675, P = 0.005). Although high stromal CD8+ TIL levels were linked to higher PFS and OS, these differences did not reach statistical significance (P = 0.114 and P = 0.079, respectively). CD4+ TILs showed no significant correlation with PFS or OS. In multivariate analysis, intratumoral CD8+ TILs remained an independent prognostic factor for PFS and OS. Subgroup analysis revealed that in patients with locally advanced disease, high intratumoral CD8+ TILs were significantly associated with improved PFS (HR 0.329; 95% CI, 0.129-0.843, P = 0.021) and OS (HR 0.209; 95% CI, 0.064-0.681, P = 0.009). Conversely, in early-stage patients, neither CD8+ nor CD4+ TILs were significantly associated with PFS or OS.ConclusionOur findings suggest that intratumoral CD8+ TILs serve as a reliable prognostic biomarker for NPC, with their prognostic value particularly pronounced in patients with locally advanced disease.